Systemic, Local, and Imaging Biomarkers of Brain Injury: More Needed, and Better Use of Those Already Established? - Carpenter, Keri L. H.; Czosnyka, Marek; Jalloh, Ibrahim; Newcombe, Virginia F. J.; Helmy, Adel; Shannon, Richard J.; Budohoski, Karol P.; Kolias, Angelos G.; Kirkpatrick, Peter J.; Carpenter, Thomas Adrian; Menon, David K.; Hutchinson, Peter J. (Frontiers in Neurology, 2015)
Much progress has been made over the past two decades in the treatment of severe acute brain injury, including traumatic brain injury and subarachnoid haemorrhage, resulting in a higher proportion of patients surviving with better outcomes. This has arisen from a combination of factors. These include improvements in procedures at the scene (pre-hospital) and in the hospital emergency department, advances in neuromonitoring in the intensive care unit, both continuously at the bedside and intermittently in scans, evolution and refinement of protocol-driven therapy for better management of patients, and advances in surgical procedures and rehabilitation. Nevertheless, many patients still experience varying degrees of long-term disabilities post-injury with consequent demands on carers and resources, and there is room for improvement. Biomarkers are a key aspect of neuromonitoring. A broad definition of a biomarker is any observable feature that can be used to inform on the state of the patient, e.g. a molecular species, a feature on a scan, or a monitoring characteristic e.g. cerebrovascular pressure reactivity index. Biomarkers are usually quantitative measures, which can be utilised in diagnosis and monitoring of response to treatment. They are thus crucial to the development of therapies and may be utilised as surrogate endpoints in Phase II clinical trials. To date, there is no specific drug treatment for acute brain injury, and many seemingly promising agents emerging from pre-clinical animal models have failed in clinical trials. Large Phase III studies of clinical outcomes are costly, consuming time and resources. It is therefore important that adequate Phase II clinical studies with informative surrogate endpoints are performed employing appropriate biomarkers. In this article we review some of the available systemic, local and imaging biomarkers and technologies relevant in acute brain injury patients, and highlight gaps in the current state of knowledge.